Synthesis of some 3-phenyl chromenone-crown ethers and equilibrium studies on complexation with ion-pair extraction of sodium and potassium dyes - ÖZER, METİN (ELSEVIER SCI LTD, 2004)
6,7-Dihydroxy-3-phenyl-2H-chromenones and 7,8-dihydroxy-3-(methoxyphenyl)-2H-chromenones, o-dihydroxy-3-phenylcoumarins, were prepared from phenylacetic acid/2,4,5-trihydroxybenzaldehyde, methoxyphenylacetic acid/2,3,4-trihydroxybenzaldehyde in NaOAc/Ac2O, respectively. 3-Aryl-6,7-dihydroxy-2H-chromenone and 3-aryl-7,8-dihydroxy-2H-chromenone reacted with the polyethylene glycol ditosylate in CH3CN/Me2CO3 to afford 12-crown-4,15-crown-5, and 18-crown-6-chromenones. The purified products were identified with IR, (NMR)-N-1, low and high resolution mass spectroscopy and elemental analysis. Liquid-liquid extractive-spectrophotometric studies of sodium and potassium ion complexes of 3a-c, 4a-h coumarin-crown ethers and anionic dyes [4-(2-pyridylazo)-resorcinol monosodium salt monohydrate (SPAR), and sodium picrate (SP), and potassium picrate (PP)], as the counter ion are described. The overall extraction equilibrium constants for the 1:1 complexes of the above coumarin-crown ethers with sodium and potassium ions, between the organic solvent and water, have been determined at 25 C. They were conducted in various solvent-water systems maintaining an identical initial cation concentration in water, [MD]W, and a macrocyclic ligand concentration in the organic phase, [L-0](org), so that in all extractions [M-0(+)](W):[L-0](org) ratios were 1:1. An ion association complex formed between the alkali-crown ether complex ion and a dye anion was extracted into the CH2Cl2 organic solvent, and then the dye concentration of the separated aqueous phase was measured with an ultraviolet-visible spectrophotometer. According to the study, SPAR is the best associated dye with all the coumarin-crown ethers and the extracted dye occurs as the ion-pair complex. The extraction selectivity was interpreted quantitatively by the constituent equilibrium constants, i.e. K-ext, the ion-pair extraction constant of ML+ and A(-) in CH2Cl2. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: 3-phenyl-chromenone crown ethers; coumarin-crown ethers; Na+,K+-complexation; ion-pair solvent extraction; sodium and potassium dyes; RELAXATION-TIME MEASUREMENTS; DIPOLE INTERACTION MECHANISM; ALKALI-METAL PICRATES; SOLVENT-EXTRACTION; MACROCYCLIC ETHERS; METHANOL-D; 18-CROWN-6; WATER; POLYETHERS; 15-CROWN-5